1991
DOI: 10.1002/app.1991.070431003
|View full text |Cite
|
Sign up to set email alerts
|

Nylon 4/PVA blend membrane for dialysis

Abstract: SYNOPSIST o improve the hydrophilicity and enhance the transport flux of nylon 4 membrane for dialysis, this study attempts to utilize blending nylon 4 with poly (vinyl alcohol) (PVA) .The instability of PVA in water can be significantly improved by esterification of PVA with formic acid when it is used as casting solvent of PVAInylon 4 blend membrane. By this method, the stability of PVA in water can be obtained more easily than by other methods, such as chemical, y-ray irradiated crosslinking, or high-temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 22 publications
2
6
0
Order By: Relevance
“…Among the various methods of producing high ionic conduction, polymer blend is a valid and feasible approach. 9,10 In agreement with Wieczorek and coworkers, 11,12 the addition of particles (fillers) produces changes in the vitreous transition temperature that alternate the temperature dependence of crystallization and in the ionic conduction of the material.…”
Section: Introductionsupporting
confidence: 81%
“…Among the various methods of producing high ionic conduction, polymer blend is a valid and feasible approach. 9,10 In agreement with Wieczorek and coworkers, 11,12 the addition of particles (fillers) produces changes in the vitreous transition temperature that alternate the temperature dependence of crystallization and in the ionic conduction of the material.…”
Section: Introductionsupporting
confidence: 81%
“…Other authors improved the instability of the PVA/nylon-4 polymer blend for dialysis by esterfication of PVA with formic acid, which was used as a common casting solution. 6 They reported that this method is easier than chemical, ␥ radiation crosslinking, or high-temperature treatment. Also, other authors investigated the effects on the formation of conjugated double bonds in the thermal degradation of PVA blends with poly(vinyl chloride) using UV absorption and IR spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogels may be chemically stable or they may degrade and eventually disintegrate and dissolve. These hydrophilic materials are also coined as "hungry networks" and have been widely employed in variety of applications such as artificial implants, 1 in medicine and pharmacy, agriculture, controlled drug delivery systems, 2 dialysis membranes, 3 burn dressings, 4 etc. To serve as biomaterials the hydrogel must meet certain prerequisites such as adequate water sorption, good mechanical performance, and above all, a fair level of blood compatibility.…”
Section: Introductionmentioning
confidence: 99%